Understanding displacement of onboard contingents in Navy amphibious ships - Martinez-Grueira, Heitor; Asorey-Cacheda, Rafael; Garcia-Sanchez, Antonio-Javier; Garcia-Haro, Joan (PLOS ONE, 2025)
The Naval Ship Code (NSC) was enacted in 2009 to standardize regulations for NATO member naval forces, and a study commissioned by the Spanish Navy General Staff (EMA) aimed to identify the factors that influence onboard personnel’s ability to move during an evacuation process. This study validated the soundness of the safety protocols implemented on navy vessels and highlighted the impact of certain characteristics of the embarked military contingent, such as body mass index, age, and seniority. It also found that such characteristics could act as distinctive factors among the embarked contingents in the evacuation of a military vessel. The study quantified the effect of these intervening characteristics, confirming the need for different displacement models for each of the study contingents to improve ship evacuation maneuvers. The findings of this study provide insights into the behavior of different embarked contingents during the evacuation process and can inform the development of more effective safety protocols for military naval operations. The starting hypothesis is that certain characteristics of the embarked military contingent have a decisive influence on their displacement capacity during the evacuation process. This hypothesis has been expanded in the sense that these same characteristics can act as differentiating elements among the embarked contingents evacuating a military vessel. It is possible to quantify the influence of these characteristics and implement a displacement model applicable in escape, evacuation, and rescue processes. Thus, the specific characteristics of a study contingent will be reflected in its displacement model. In this article we find that while members of the landing force (LF) show greater displacement capacity through a longitudinal corridor (around 10%), their ability to overcome other passage elements present on the study vessel is reduced (around 30%) compared to members of the vessel’s own crew.